Northanger Abbey - Austen, Jane, 1775-1817 (Vintage Classics, 2007)
Northanger Abbey is both a perfectly aimed literary parody and a withering satire of the commercial aspects of marriage among the English gentry at the turn of the nineteenth century. But most of all, it is the story of the initiation into life of its nave but sweetly appealing heroine, Catherine Morland, a willing victim of the contemporary craze for Gothic literature who is determined to see herself as the heroine of a dark and thrilling romance. When Catherine is invited to Northanger Abbey, the grand though forbidding ancestral seat of her suitor, Henry Tilney, she finds herself embroiled in a real drama of misapprehension, mistreatment, and mortification, until common sense and humor and a crucial clarification of Catherines financial status puts all to right. Written in 1798 but not published until after Austen's death in 1817, Northanger Abbey is characteristically clear headed and strong, and infinitely subtle in its comedy.